(untitled) (Journal of the College of Basic Education, 2023)
Speech is a means of communication intended to convey meaning in order to exchange ideas, and this necessitates that there be proportionality between the word and the meaning it denotes, and there must also be harmony between the signifier and the idea it carries, and the context in which it is contained. It witnesses a clear and remarkable semantic consistency, and one of the forms of this semantic consistency is the semantic coloration that follows the change in the reading of some words in the hadeeth text. The parsing aspect, and this is what this research has proven. It has been shown that there are phenomena in the hadith text that differ in their reading, and this difference led to a difference in the lexical meaning. The recitation of the word and the difference in its meaning may not change its compatibility with the text in which it was mentioned, or it may change slightly, which in turn helps to strengthen the other reading of the word. This is what we found by analyzing the hadith texts that included semantic phenomena that differed in their reading.